PERBAIKAN SIFAT FISIKO-KIMIA TANAH PSAMMENT DENGAN PEMULSAAN ORGANIK DAN OLAH TANAH KONSERVASI PADA BUDIDAYA JAGUNG - Adrinal Adrinal; Amrizal Saidi; Gusmini Gusmini (Jurnal Solum, 2012)
A research about amelioration of psycho-chemical of Psamment by using organic mulch and techniques of conservation tillage on corn growth had been conducted in 2009. Field experiment was located in Korong Olo Bangau, Batang Anai, Padang Pariaman Regency. The general objective of the research was to improve fertility of Psamment and to find out the best tillage practice for corn growth based on soil and water conservation rules. The treatment consisted of two factors (3 x 5) which was designed in RBD. The first factor was tillage (No till, Minimum till, convensional till) and the second factor was mulch source (without mulch, Tithonia, Chromolaena, rice straw, and corn straw). Parameters analysed were either soil physical (moisture, BD, total pore, aggregation) or chemical (pH, N, P, and K) properties, as well as crop production. The result showed that both treatments were able to improve soil-physico-chemical properties of Psamment and corn yield. The value of BD decreased, soil organic mattere, total pore, and aggregation increased. Then, the soil pH as well as available P and K tended to increase. The highest yield (dry seeds) was found from combination between minimum tillage and tithonia mulch.Keywords: sifat fisiko-kimia, Psamment, mulksa, olah tanah konservasi, jagung.